Choosing Democracy: The 1955 General Election in Medan, Indonesia - Syaputra, Yandi; Agustono, Budi; Pujiati, Pujiati (Paramita: Historical Studies Journal, 2024)
This study analyzes the 1955 General Election in Medan, the inaugural democratic exercise in post-independence Indonesia. Aimed at understanding the era's political dynamics and voter behavior, the research focuses on the electoral process, party strategies, and the socio-economic context influencing the elections. The study uses historical analysis to draw on primary sources, including governmental decrees and local newspaper archives, alongside secondary literature on Indonesian political history. The method involves a chronological examination of events leading to the elections, political parties' roles, and socioeconomic factors that impact voter preferences. The results reveal that the 1955 General Election in Medan was a complex and multifaceted event shaped by the legacy of colonial and wartime experiences. Political parties like Masyumi, PKI, and PNI employed diverse strategies to engage with voters, ranging from religious politics to nationalist rhetoric. Despite land disputes and economic instability, the elections saw high voter turnout and active participation, culminating in Masyumi’s victory. In conclusion, the 1955 General Election in Medan was pivotal in Indonesia’s democratic journey, reflecting the interplay between historical legacies, political aspirations, and the people's collective will. It began a new era in Indonesian politics, characterized by active public engagement and the establishment of a representative democratic system.Penelitian ini menganalisis Pemilu 1955 di Medan, pelaksanaan demokrasi perdana di Indonesia pasca kemerdekaan. Bertujuan untuk memahami dinamika politik dan perilaku pemilih pada masa itu, penelitian ini berfokus pada proses pemilu, strategi partai, dan konteks sosio-ekonomi yang mempengaruhi pemilu. Dengan menggunakan analisis sejarah, penelitian ini memanfaatkan sumber-sumber primer, termasuk keputusan pemerintah dan arsip surat kabar lokal, serta literatur sekunder mengenai sejarah politik Indonesia. Metode ini melibatkan pemeriksaan kronologis peristiwa-peristiwa menjelang pemilu, peran partai politik, dan dampak faktor sosial-ekonomi terhadap preferensi pemilih. Hasilnya menunjukkan bahwa Pemilu 1955 di Medan merupakan peristiwa yang kompleks dan memiliki banyak aspek yang dibentuk oleh warisan pengalaman kolonial dan masa perang. Partai politik seperti Masyumi, PKI, dan PNI menerapkan beragam strategi untuk menjangkau pemilih, mulai dari politik agama hingga retorika nasionalis. Meskipun terdapat tantangan seperti sengketa tanah dan ketidakstabilan ekonomi, pemilu ini menunjukkan tingkat partisipasi pemilih dan partisipasi aktif yang tinggi, yang berpuncak pada kemenangan Masyumi. Kesimpulannya, Pemilu 1955 di Medan merupakan momen penting dalam perjalanan demokrasi Indonesia, yang mencerminkan keterkaitan antara warisan sejarah, aspirasi politik, dan kemauan kolektif masyarakat. Hal ini menandai dimulainya era baru dalam politik Indonesia, yang ditandai dengan keterlibatan publik yang aktif dan pembentukan sistem demokrasi perwakilan.